Exposure to Sub-Inhibitory Concentrations of Cefotaxime Enhances the Systemic Colonization of Salmonella Typhimurium in Balb/C Mice - Reyes-Cerpa, S (Royal Society of London, 2015)
It has been proposed that sub-inhibitory concentrations of antibiotics play a role in virulence modulation. In this study, we evaluated the ability of Salmonella enterica serovar Typhimurium (hereafter S. Typhimurium) to colonize systemically BALB/c mice after exposure to a sub-inhibitory concentration of cefotaxime (CTX). In vivo competition assays showed a fivefold increase in systemic colonization of CTX-exposed bacteria when compared to untreated bacteria. To identify the molecular mechanisms involved in this phenomenon, we carried out a high-throughput genetic screen. A transposon library of S. Typhimurium mutants was subjected to negative selection in the presence of a sub-inhibitory concentration of CTX and genes related to anaerobic metabolism, biosynthesis of purines, pyrimidines, amino acids and other metabolites were identified as needed to survive in this condition. In addition, an impaired ability for oxygen consumption was observed when bacteria were cultured in the presence of a sub-inhibitory concentration of CTX. Altogether, our data indicate that exposure to sub-lethal concentrations of CTX increases the systemic colonization of S. Typhimurium in BALB/c mice in part by the establishment of a fitness alteration conducive to anaerobic metabolism. © 2015 The Authors.